2018
DOI: 10.1590/1807-3107bor-2018.vol32.0110
|View full text |Cite
|
Sign up to set email alerts
|

Can implant surfaces affect implant stability during osseointegration? A randomized clinical trial

Abstract: This randomized clinical trial evaluated the insertion torque (IT), primary, and secondary stability of dental implants with different surface treatments during the osseointegration period. Nineteen patients with bilateral partial edentulism in the posterior mandibular region were randomly allocated to two implant brand groups and received implants with different surface treatments in the opposite site of the arch: Osseotite and Nanotite or SLA and SLActive. During implant placement, the maximum IT was recorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 36 publications
2
10
0
6
Order By: Relevance
“…The long-term outcomes of this study indicate successful bone integration to the implants and agree with the reported results of other experimental and clinical studies with acid-etched surface implants [34][35][36][37]. An in vitro experimental study compared the chemical composition and microstructural configuration of dental implants subjected to two different surface treatments: sandblasting with alumina and acid-etching with hydrofluoric and nitric acids [34].…”
Section: Discussionsupporting
confidence: 87%
“…The long-term outcomes of this study indicate successful bone integration to the implants and agree with the reported results of other experimental and clinical studies with acid-etched surface implants [34][35][36][37]. An in vitro experimental study compared the chemical composition and microstructural configuration of dental implants subjected to two different surface treatments: sandblasting with alumina and acid-etching with hydrofluoric and nitric acids [34].…”
Section: Discussionsupporting
confidence: 87%
“…The present study is in agreement with findings of previous randomized clinical trials reporting acceptable primary stability with mean ISQ values of above 75 N/cm in humans. 53 The bone density, implant size and macro-scale geometry of the implant body greatly affect the ISQ values and, as we used the same implant size and receptor area, similar levels of ISQ between the evaluated groups were confirmed. 54 A clinical…”
Section: Dovepressmentioning
confidence: 52%
“…Sim and Lang investigated the influence of bone density structure and implant length on stability levels, and reported that the length of the implant influences the implant stability only at the time of the surgery and has lesser impact on further stages of osteointegration. Conversely, bone density seems to influence the stability level in a greater way and on all stages of osteointegration [17]. Subsequently, to standardize the sample population, we selected homogenous bone sites of the frontal aspect of the maxilla as a region of interest.…”
Section: Discussionmentioning
confidence: 99%